Attentional decoupling while pursuing intentions: a form of mind wandering? - Cohen, Anna-Lisa (Frontiers in Psychology, 2013)
In the current study, participants performed an ongoing lexical decision task (LDT) in which they had to classify letter strings as words or nonwords. In intention conditions, they also had to encode a postponed intention to remember to make a different response if a pre-specified cue appeared. Attempting to replicate an important finding from Cohen, Jaudas, and Gollwitzer (2008), the interest was in examining how varying cognitive load associated with an intention influences attention to the ongoing task (measured by reaction times). Typically, disengaging from a primary task is perceived as negative as it can lead to performance decrements; however, if disengaging from a primary task helps one to accomplish a desired future goal, then these attentional shifts may in fact be constructive. Results replicated those of Cohen et al. (2008) and showed that participants were very flexible in how they managed attention in the ongoing lexical decision task. Reaction time costs emerged when cognitive load was high and solely for word trials (i.e., not for nonword trials). The implications for mind wandering are that, while our attention may wander when stimuli are present that trigger a suspended or unfulfilled goal, we are better able to stay on task when the stimuli are less goal relevant. Therefore, the decoupling process (e.g., Schooler et al., 2011) might be initiated when postponed goals are accompanied by a high degree of cognitive load and when external stimuli are present that relate to that goal.